The Myths of Modern Medicine: The Alarming Truth about American Health Care - Leifer, John (Rowman & Littlefield Publishers, 2014)
The American health care system is terminally ill. It is astonishingly expensive, remarkably variable in quality, and incapable of stemming the rising tide of chronic illness in our population. Yet, the majority of Americans believe it is the best system in the world and cling to the belief that, far from ailing, it delivers care superior to those of countries across the globe. The system has obliged us by providing an elaborate set of myths and misconceptions about American health care that significantly shape our beliefs. These myths keep us blissfully ignorant about the true quality, safety, and value of the care we receive. This ignorance has a price: it leads us to draw erroneous conclusions about our conditions, fail to properly evaluate potential treatment options, and rarely question our providers’ competency. The Myths of Modern Medicine looks at the real issues contributing to the dysfunction of our healthcare system and how these issues affect the care we receive. The book, based upon John Leifer’s 30 years of immersion in the healthcare industry, challenges some of our most commonly held misperceptions about this vitally important industry. Leifer strips away the elaborately constructed myths that conceal the ugly underbelly of healthcare and lays bare the truth about an industry that serves special interest groups far better than it serves its patients. A survival guide for anyone entering the healthcare system, this timely work helps consumers better research provider competency; ask the right questions to evaluate potential treatment options; and communicate the information that will help yield the right treatment decisions. Several studies have shown patients today have only about a 50 percent chance of getting the generally accepted best treatment for their conditions. This book helps consumers increase these odds with step-by-step directions on how to interact more productively with their doctors and become true partners in making what may be the most crucial decisions of their lives.